Protein-Based Films with Different Glycerol Concentrations: Thickness, Gelation Time and Microstructure - Ayunita, Novi; Fahrullah, Fahrullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Edible films are thin films made of hydrophilic materials such as protein, which function as packaging materials that provide a preservation effect, act as a barrier to oxygen, reduce water evaporation, and improve product appearance. The objective of this study was to ascertain the impact of varying glycerol concentrations on the thickness, gelation time, and microstructure of protein-based films. This study employed a Completely Randomized Design with three treatments and three replicates. The treatments consisted of G1: 1.25 ml glycerol; G2: 1.5 ml; and G3: 1.75 ml. The protein-based film produced thickness values of 0.215-0.288 mm, gelation time of 1380-1381 seconds and uniform microstructure. The glycerol concentration of 1.25 ml produced the most favourable film characteristics, in comparison to other concentrations. These included a thickness value of 0.215 mm, a gelation time of 1380 seconds and a more continuous microstructure, characterised by an even distribution of the main film-forming components.